Dependable Computing - EDCC 2020 Workshops: AI4RAILS, DREAMS, DSOGRI, SERENE 2020, Munich, Germany, September 7, 2020, Proceedings - Bernardi, Simona; Vittorini, Valeria; Flammini, Francesco; Nardone, Roberto; Marrone, Stefano; Adler, Rasmus; Schneider, Daniel; Schleiß, Philipp; Nostro, Nicola; Løvenstein Olsen, Rasmus (Dependable Computing - EDCC 2020 Workshops AI4RAILS, DREAMS, DSOGRI, SERENE 2020, Munich, Germany, September 7, 2020, Proceedings, 2020)
This book constitutes refereed proceedings of the Workshops of the 16th European Dependable Computing Conference, EDCC: ?Workshop on Articial Intelligence for Railways, AI4RAILS 2020, Worskhop on Dynamic Risk Management for Autonomous Systems, DREAMS 2020, Workshop on Dependable Solutions for Intelligent Electricity Distribution Grids, DSOGRI 2020, Workshop on Software Engineering for Resilient Systems, SERENE 2020, held in September 2020. Due to the COVID-19 pandemic the workshops were held virtually. The 12 full papers and 4 short papers were thoroughly reviewed and selected from 35 submissions. The workshop papers complement the main conference topics by addressing dependability or security issues in specic application domains or by focussing in specialized topics, such as system resilience.